ICTE 2019 : proceedings of the sixth International Conference On Transportation Engineering, September 20-22, 2019, Chengdu, China - Liu, Xiaobo, 1974-; Peng, Qiyuan; Wang, Kelvin C. P. (American Society of Civil Engineers, 2020)
This collection contains 127 peer-reviewed papers on diverse transportation engineering issues. Topics include: transportation planning and socio-economic development; traffic control and information technology; sustainable transportation methods; rail transit and high-speed rail operations; logistics and supply chain management; and transportation equipment performance and organization optimization. This collection will be of interest to transportation researchers and practitioners as well as transportation planners and government officials.
Sponsored by School of Transportation and Logistics, Southwest Jiaotong University, National United Engineering Laboratory of Integrated and Intelligent Transportation, Southwest Jiaotong University, National Engineering Laboratory of Integrated Transportation Big Data Application, Southwest Jiaotong University, the Transportation & Development Institute (T & DI) of the American Society of Civil Engineers (ASCE).
Keywords: Transportation engineering -- Congresses.; Traffic engineering -- Congresses.; Traffic congestion -- Management -- Congresses.; High speed trains -- Congresses.; Street-railroads -- Congresses.; Business logistics -- Congresses.; Urban transportation -- Passenger traffic -- Congresses.; Traffic safety -- Congresses.; elektronické knihy; electronic books